The Exploring Speech Disfluency Patterns in 10th Grade Students at Samal National High School (International Journal of Theory and Application in Elementary and Secondary School Education, 2023)
This research aimed to determine the everyday speech disfluencies of the Grade Ten students of Samal National High School. Specifically, this study aimed to discover and describe the typology of speech disfluencies in tenth graders. The participants of this study are grade ten students from Samal National High School. Among the 100 extemporaneous speeches of the respondents, 25 purposively selected speeches were subjected to analysis. The analysis revealed ten typologies of speech disfluencies committed in speeches. These are prolongation, blocks, Interjection petition of words, repetition of a phrase, repetition of a syllable, restarts code-switching, and stutStutteringe Possible causes of these disfluencies are mother tongue interference, lack of knowledge of the target language, hesitation, and low vocabulary. With these, language teachers should continuously find strategies to help the students overcome or at least lessen the identified speech disfluencies in discourse and language learning.